Modelling real‐world effects in near‐field SAR collections for compressive sensing - Price, George A. J.; Andre, Daniel; Moate, Chris; Yuen, Peter W. T.; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2025)
The ability to control sidelobes in a SAR image is critical to forming images that are useful for interpretation and exploitation. QinetiQ has developed the RIBI sensing system, which utilises a distributed coherent array of sensors to produce multistatic images. These systems require techniques from outside the traditional radar domain to utilise the theoretical resolution possible in synthesising a coherent aperture from multiple disparate collections. This paper develops previously published work on using compressive sensing techniques to suppress sidelobes in SAR images to develop a higher‐fidelity measurement model. Using Cranfield University's GBSAR System a series, experimental measurements are conducted, and image estimation techniques are applied to this real data. It demonstrates an improvement in recovery performance over an isotropic measurement matrix, and discusses areas which require further development.
Keywords: 4013 Geomatic Engineering; 40 Engineering; Networking & Telecommunications; 4006 Communications engineering